The Trends of Fiscal Policy in bearing the financial burden of the government and the Extent Leadership in Iraq during the period 2004- 2014 - عبد اللطيف, عماد محمد علي; مجيد, عامر عبد الله (Journal of Economics and Administrative Sciences, 2017)
AbstractThere has been a heated controversy over the role the financial policy plays and how sufficient   it   is   in affording   the   financial   burden. This   burden   is   known as the operational   current expenses   which   the   governments   of   various countries mainly afford,   despite the   discrepancy   in   the   government’s   economic   policy.   After   the deterioration and deficit in the state budget in all countries nowadays, it was necessary to find an appropriate mechanism so as to achieve the interaction and appropriateness between the main instruments of the financial policy on the realistic level with regard to their economy.This research aims to analyses the relationship between the main instruments of the State policy to encounter the increasing financial burden on the government,   where the developing countries’ economy in general and Iraq’s in particular suffers from the financial   policy’s   inefficacy   and   feebleness   due   to   the   fluctuation   of   these governments’ policies. In addition, there is a lack of credibility for these governments to achieve a noticeable improvement that could    create economic stability; especially most   of   the   decisions   made   regarding   the   financial   policy   tend   to   be   under   the influence of policy makers.The study concludes that Iraq has been partially able to afford its operational expenses in spite of the economic, political, social, and security challenges it faced. Further, there was no active financial policy and a clear vision for attempting to diversify the revenue resources to depend on instead of depending on oil as the main source for taking   the   financial   burden.   In   addition,   Iraq   economy   suffers from a structural imbalance that negatively affects its capacity to   diversify the revenues resources, while the financial policy has a significant place among other policies because it can play the greatest role in achieving the multiple objectives and thus achieve economic stability.